Synsedimentary broken‐foreland tectonics during the Paleogene in the Andes of NW Argentine: new evidence from regional to centimetre‐scale deformation features. (7th September 2016) - Montero‐López, Carolina; del Papa, Cecilia; Hongn, Fernando; Strecker, Manfred R.; Aramayo, Alejandro
Abstract: Unravelling the spatiotemporal evolution of the Cenozoic Andean (Altiplano‐Puna) plateau has been one of the most intriguing problems of South American geology. Despite a number of investigations, the early deformation and uplift history of this area remained largely enigmatic. This paper analyses the Paleogene tectono‐sedimentary history of the Casa Grande Basin, in the present‐day transition zone between the northern sector of the Puna Plateau and the northern part of the Argentine Eastern Cordillera. Our detailed mapping of synsedimentary structures records the onset of regional contractional deformation during the middle Eocene, revealing reactivation of Cretaceous extensional structures and the development of doubly vergent thrusts. This is in agreement with records from other southern parts of the Puna Plateau and the Eastern Cordillera. These observations indicate the existence of an Eocene broken foreland setting within the region, characterized by low‐lying compressional basins and ranges with spatially disparate sectors of deformation, which was subsequently subjected to regional uplift resulting in the attainment of present‐day elevations during the Neogene.